Legal Dilemma of Interfaith Marriage: A Study on Regulation and Implementation in Indonesia - Prameswari Annisa Putri; Siska Septiria Nosari; Fadlan Fadlan (Green Social: International Journal of Law and Civil Affairs, 2024)
This study examines the complex legal framework surrounding interfaith marriages in Indonesia, focusing on the intersection of religious law, civil law, and cultural practices. Through analysis of existing regulations, court decisions, and implementation practices, the research investigates the challenges faced by couples seeking interfaith marriages within Indonesia's pluralistic legal system. The study employs a qualitative methodology, combining doctrinal legal research with empirical data collected through case studies and interviews with legal practitioners, religious authorities, and couples who have navigated the interfaith marriage process. Findings reveal significant disparities between formal regulations and practical implementation, highlighting how legal ambiguities and administrative barriers often lead couples to seek alternative solutions, including overseas marriages or religious conversion. The research demonstrates that while Indonesia's constitution guarantees freedom of religion and the right to marry, the practical implementation of interfaith marriage regulations remains problematic due to conflicting interpretations of religious and civil law. The study concludes that current regulatory frameworks inadequately address the contemporary realities of Indonesia's diverse society, suggesting the need for legal reform that better balances religious principles with citizens' constitutional rights.